2017
DOI: 10.1080/00913847.2017.1358585
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative management of ulnar collateral ligament injuries in the throwing athlete

Abstract: Medial ulnar collateral ligament (UCL) injuries have become increasingly prevalent in overhead athletes. The orthopaedic literature contains a wealth of information on operative management of these injuries. However, there are few high-quality longitudinal studies on non-operative care of UCL injuries. The purpose of this review is to describe the non-operative approach to managing UCL injuries, including recommended rehabilitation strategies and predictors of successful non-operative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…12 Additional prospective investigations have demonstrated that abnormalities at routine preseason magnetic resonance imaging examinations are found in 35% to 48% of young baseball players, with abnormalities more often found in those players who receive private coaching and who play year round. 21,22 Patients with persistent pain who have failed a thorough nonsurgical rehabilitation approach, including a graded return to throwing, 24 and who have additional specific examination findings, such as a positive valgus or moving valgus stress test, are candidates for advanced imaging. After imaging, the authors assert that the patient's symptoms and clinical presentation must be carefully integrated in evaluating radiological results.…”
Section: Imagingmentioning
confidence: 99%
“…12 Additional prospective investigations have demonstrated that abnormalities at routine preseason magnetic resonance imaging examinations are found in 35% to 48% of young baseball players, with abnormalities more often found in those players who receive private coaching and who play year round. 21,22 Patients with persistent pain who have failed a thorough nonsurgical rehabilitation approach, including a graded return to throwing, 24 and who have additional specific examination findings, such as a positive valgus or moving valgus stress test, are candidates for advanced imaging. After imaging, the authors assert that the patient's symptoms and clinical presentation must be carefully integrated in evaluating radiological results.…”
Section: Imagingmentioning
confidence: 99%
“…Tear location is another important factor to consider when considering nonoperative management. Proximal tears or avulsions in general offer a better prognosis with nonoperative treatment 10. When nonoperative management fails, reconstruction or repair of the UCL is indicated.…”
Section: Introductionmentioning
confidence: 99%
“…Proximal tears or avulsions in general offer a better prognosis with nonoperative treatment. 10 When nonoperative management fails, reconstruction or repair of the UCL is indicated. Historically, reconstruction, using either autograft or allograft tendon to replace the deficient UCL, otherwise known as a Tommy John procedure, has yielded reliable long-term results and remains the gold standard for surgical treatment.…”
mentioning
confidence: 99%